Explorando as propriedades eletrônicas e topológicas do cristal Bi2Se3 dopado com alumínio - Okuma, Luíza Tiemi Pacheco (2024)
In this work, motivated by experimental evidence of ARPES carried out by our collaborators at UFES, theoretical electronic structure calculations were carried out about the electronic and topological properties of bismuth selenide, Bi2Se3, doped with aluminum. A brief review of the literature is presented on the bases for the Density Functional Theory (DFT) and how this approach is built within the Born-Oppenheimer approximation. In addition, a discussion is made regarding the topology of materials and their main mathematical entities, with the aim of understanding some properties of topological materials. The artifices used to confirm the topologically non-trivial character of Bi2Se3 underwent calculation of the topological invariant Z2, in addition to the analysis: 1) of the surface states; 2) the orbital composition of the band inversion around the Γ point; and 3) the band structure for a system with few layers. Following these steps, it was possible to infer the role of the substitution of Bi by Al in the insulator Bi2Se3